Manajemen Madrasah Diniyah TPQ Miftahul Huda Krakal - Alian - Bahrun Ali Murtopo; Syifa Maulana (LPPM IAINU Kebumen, 2019)
Research in an Islamic educational institution about management is very important to know and understand the concepts and principles and functions of management. Research conducted at TPQ Miftahul Huda Krakal, Alian, Kebumen is an old educational institution, but only recently legalized recently. Specifically the research emphasizes the concept of planning until its implementation. With this research is expected we will know how a management concept in Islamic educational institutions planned until the implementation. This research is qualitative and quantitative by using method of interview, documentation, and observation. The results of research in TPQ Miftahul Huda began to show a pretty good development, although there are some parts of infrastructure facilities are lacking, but it does not reduce the spirit to continue to implement learning.